2001
DOI: 10.1046/j.1467-2960.2001.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

The implications of solar UV radiation exposure for fish and fisheries

Abstract: Ultraviolet radiation (UVR) possesses three important properties that combine to make it a potent environmental force. These include the potential to induce damage: UVR carries more energy per photon than any other wavelength reaching the Earth’s surface. Such highly energetic photons are known to damage many biological molecules, such as DNA and proteins. In addition, they can initiate a series of redox reactions to form reactive oxygen species (ROS), which cause oxidative stress to cells and tissues. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 83 publications
(141 reference statements)
2
71
1
Order By: Relevance
“…Recent work suggests that the early life history stages of fishes and invertebrates are particularly sensitive to the UV radiation present in natural sunlight (Lesser et al 2001;Zagarese and Williamson 2001). The positive correlation between solar radiation and PLD was consistent with the negative relationship between solar radiation and otolith growth up to 25 days, since a longer larval duration is likely to be a consequence of decreased growth.…”
Section: Pelagic Larval Durationmentioning
confidence: 67%
See 2 more Smart Citations
“…Recent work suggests that the early life history stages of fishes and invertebrates are particularly sensitive to the UV radiation present in natural sunlight (Lesser et al 2001;Zagarese and Williamson 2001). The positive correlation between solar radiation and PLD was consistent with the negative relationship between solar radiation and otolith growth up to 25 days, since a longer larval duration is likely to be a consequence of decreased growth.…”
Section: Pelagic Larval Durationmentioning
confidence: 67%
“…Recent work, however, has shown that high levels of light may negatively affect fish larvae. Ultraviolet radiation may induce direct damage to the DNA and proteins of eggs and larvae, causing reduced growth or death (Lesser et al 2001;Zagarese and Williamson 2001). Moreover, Boeuf and Le Bail (1999) suggest that beyond an upper intensity, sunlight may decrease growth and even be deadly due to negative impacts on visual development, which in turn will affect feeding activities and prey selection.…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet radiation (UV, 280 to 400 nm) is damaging to fishes (Siebeck et al 1994, Lesser et al 2001, Zagarese & Williamson 2001. Shallow-dwelling marine fishes possess UV-absorbing compounds in their mucus, presumably to protect them from harmful UV (Zamzow & Losey 2002, Zamzow 2003, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The light-filtering properties of the ocular media are attributed to a group of UV-absorbing pigments called mycosporinelike amino acids (MAAs), one of which, asterina-330, has been identified in shark lenses (Dunlap et al, 1989;Douglas and Marshall, 1999). Short-wavelength-filtering ocular media can be advantageous for species inhabiting bright light environments, as UV radiation is damaging to ocular tissue (Walls and Judd, 1933;Dunlap et al, 1989;Douglas and Marshall, 1999;Lesser et al, 2001;Zagarese and Williamson, 2001). However, unless S. mitsukurii undergoes vertical migrations from its deep-water habitat into shallow water, photo-protection from UV light appears an unnecessary adaptation (Frank and Widder, 1996).…”
mentioning
confidence: 99%